End-of-life care stress in korean pediatric nurses: A cross-sectional analysis of related perceptions, attitudes, and self-efficacy - Eul A. Shin; Eun Jung Kim (PLoS ONE, 2026)
Pediatric end-of-life (EOL) care imposes a significant emotional burden on nurses, often leading to elevated stress. Psychological factors, such as perception, attitude, and self-efficacy, are known to play critical roles in stress responses during EOL care in clinical settings. This study examined the effect of South Korean pediatric nurses’ perceptions, attitudes, and self-efficacy regarding EOL care on their stress levels. A cross-sectional survey was conducted involving 150 pediatric nurses working at two university hospitals in South Korea. Structured, self-administered questionnaires were used to assess their perceptions of EOL care (supportive and obstacle factors), attitudes, and self-efficacy. Data were analyzed using t-tests, ANOVA, Scheffé’s post hoc test, and Pearson’s correlation analysis. The mean pediatric EOL care stress score was 3.60 out of 5, indicating a moderate to high level of stress. Significant differences in stress were observed based on whether participants had experienced the death of a patient in their care within the previous year and whether they had received education related to EOL care. Specifically, nurses without such experiences reported significantly higher levels of stress. Correlation analysis further revealed that pediatric EOL care stress was positively associated with supportive care perception factors and obstacle perception factors, while showing a significant negative correlation with self-efficacy. No significant relationship was found between attitudes toward EOL care and stress. This study identified the major psychological and experiential factors influencing pediatric nurses’ stress related to pediatric EOL care within two tertiary hospitals in South Korea. These findings highlight the need for structured educational interventions and institutional support systems to strengthen nurses’ coping abilities and enhance the overall quality of pediatric EOL care. In particular, integrating structured EOL training into undergraduate nursing curricula and continuing professional development programs may help reduce stress, improve self-efficacy, and ultimately ensure higher-quality pediatric EOL care.